An Analysis of Personal Pronouns Used by The Students in Writing Narrative Text at Senior High School - Siska, Widia (Ideas Publishing, 2024)
The research objective was to find out how personal pronouns used by the students in writing narrative text at SMAN 2 Koto Baru, Dharmasraya. The research method was descriptive qualitative method. The data source was documents. There were 38 sheets of student writing about narrative text. The research finding was the students still made mistakes in using personal pronouns such as subject pronoun (correct 61.1%), object pronoun (correct 32.2%), possessive adjective pronoun (correct 49.7%), possessive pronoun (correct 0%) and reflexive pronoun (correct 0%). It can be concluded the ability of the students in using personal pronouns still less.